Macroeconomic and Institutional Determinants of Non-performing Loans - Svetozar Tanasković; Maja Jandrić (Journal of Central Banking Theory and Practice, 2015)
This paper aims to analyse macroeconomic and institutional empirical determinants of growth of NPL ratios. Research is focused on selected CEEC and SEE countries in the period 2006-2013. For our analysis we use static panel model approach with the logarithm of share of NPLs to total loans as a dependent variable. As independent variables we used a combination of country-specific macroeconomic and financial indicators which are commonly used in reference literature, as well as relevant institutional variables. Our results show that there is a negative relationship between increases in GDP and rise of the NPL ratio. Along with GDP, foreign currency loans ratio and level of exchange rate are positively related with the increase of NPL ratio. This confirms the expectation that countries where domestic currency is not the main medium of credit placements will have larger problems with the level of NPLs, which is even more pronounced in periods of domestic currency depreciation. In the presented models, the inflation rate is reported as statistically insignificant for sample countries. In the group of institutional variables, only financial market level of development is reported as statistically significant in relation to the level of NPL - with a more developed financial market the level of NPLs should be lower.
Keywords: G20; G28; G32; F34; 330; Non-performing loans (NPLs); CESEE; financial stability; credit risk